Gambaran Pengetahuan Pencegahan Penyakit Skabies Pada Suku Waekolo Dusun Darlale Desa Wamlana Kecematan Fena Leisela Kabupaten Buru - Herlien Sinay; Abd. Rijal Lapodi; Iksan Soumena (Calory Journal Medical Laboratory Journal, 2023)
Scabies is a disease that can be transmitted directly or indirectly. Although this condition is more common in children and young adults, it can affect people of any age. Scabies is a type of skin infection caused by the Sarcoptes scabiei mite. To identify knowledge of scabies prevention in the Waekolo tribe, Wamlana village. The research method used is a quantitative method with a descriptive observation research design using a cross-sectional approach. The instrument used was the Questionnaire The results of research conducted from 70 respondents who had the highest distribution of knowledge, namely fairly good knowledge, amounted to 36 people (51.4%) and the least amounted to good knowledge, amounted to 10 people (14.3%). Public knowledge about scabies prevention, where there are still people who do not know the causes of scabies, as well as about the transmission of scabies.